ANALISIS SEMIOTIKA DALAM TEKS PERJANJIAN TELLUMPONCCOE BUDAYA BUGIS BONE - Nurandi, Muhammad; Fitriana, Irna; Idris, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to uncover the cultural meanings in the text of the Treaty of Tellumpoccoe using Roland Barthes' semiotic theory, which includes three levels of analysis: denotation, connotation, and myth. The research method used is descriptive qualitative with a semiotic approach. Data were obtained through literature study and text analysis, then interpreted using Barthes' theoretical framework. The results of the study show that in the denotative meaning, the text of the Tellumpoccoe Agreement contains practical rules regarding solidarity, prohibition of interfering in the affairs of other kingdoms, loyalty to promises, commitment to military assistance, and prohibition of seizing property. In the connotative meaning, this text reflects Bugis cultural values, such as sipakatau (humanizing each other), siri (self-respect), assitinajang (equality), pacinna (loyalty), and paccing (honesty). Meanwhile, in the mythical meaning, the Tellumpoccoe text presents the ideology of the sacred unity of the Bugis people which is eternal, strong, and has divine legitimacy through Dewata Seuwae. The conclusion of this study confirms that the Tellumpoccoe Treaty is not merely a political document, but also a representation of Bugis cultural values ​​that shape the collective identity of its people. These values ​​remain relevant today as guidelines for maintaining brotherhood, solidarity, and honor in Bugis culture amidst changing times.